Barriers to enhanced recovery after surgery (ERAS) protocol implementation: A mixed methods study of surgeon attitudes, institutional factors and patient perspectives - Varsha Raja Ayyanar (Bioinformation, 2026)
Enhanced Recovery After Surgery (ERAS) protocols improve post-operative recovery, yet their implementation remains inconsistent due to multiple barriers. Therefore, it is of interest to evaluate the surgeon attitudes, institutional factors and patient perspectives influencing ERAS protocol implementation using a mixed-methods approach. Quantitative data were collected through structured questionnaires, while qualitative insights were obtained from interviews and focus group discussions involving healthcare professionals and post-operative patients. The study identified resistance to change, inadequate institutional support, limited resources, insufficient training, communication gaps and poor patient awareness as the major barriers, although most patients expressed willingness to follow ERAS after appropriate education. Thus, data shows that addressing these barriers through targeted training, organizational support, multidisciplinary collaboration and patient education may improve ERAS adoption and surgical outcomes.